2018
DOI: 10.1103/physrevapplied.9.044025
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Excitation Transfer between Two-Dimensional Semiconductor and Molecular Layers

Abstract: The geometry-dependent energy transfer rate from an electrically pumped inorganic semiconductor quantum well into an organic molecular layer is studied theoretically. We focus on Förster-type nonradiative excitation transfer between the organic and inorganic layers and include quasimomentum conservation and intermolecular coupling between the molecules in the organic film. (Transition) partial charges calculated from density-functional theory are used to calculate the coupling elements. The partial charges des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…In the latter, above cryogenic temperatures, dephasing due to exciton-phonon, and exciton-exciton interaction are dominant compared to radiative losses, and can be calculated accordingly [18,36,38]. In Eq (8) we again make use of r M = 0 and write for the externally applied electric field…”
Section: B Near-field Solution Of the Wave Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter, above cryogenic temperatures, dephasing due to exciton-phonon, and exciton-exciton interaction are dominant compared to radiative losses, and can be calculated accordingly [18,36,38]. In Eq (8) we again make use of r M = 0 and write for the externally applied electric field…”
Section: B Near-field Solution Of the Wave Equationmentioning
confidence: 99%
“…Hybrid inorganic and organic systems (HIOS) are a promising platform for future optoelectronic applications since they combine appealing properties of two different material classes. Organic molecules show highly tunable transition energies and provide large optical dipole moments as the respective excitons are of the Frenkel type [1][2][3][4][5][6][7][8][9][10][11][12]. Transition metal dichalcogenites (TMDCs) are inorganic, atomically thin semiconductors that have stimulated research in the last years: Their atomic thickness leads to a reduced screening of the Coulomb interaction and consequently to the formation of stable, bound electron hole pairs, namely Wannier type excitons, which dominate the optical properties in the vicinity of the band edge [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…√ N m with N m the number of molecular unit cells and wave vector k [71][72][73] . At the same time, valence band electrons in the TMDC layer are described by operators v k .…”
Section: Appendix A: Hamiltonianmentioning
confidence: 99%
“…In 2D organic–inorganic quantum well systems, it is predicted that a hybrid exciton combines the large oscillator strength of the organic Frenkel exciton and the large nonlinear susceptibility of the inorganic Wannier excitons. , Several studies have shown experimental evidence of weak exciton hybridization through efficient energy transfer. Due to the dependence on the thickness of the barrier separating the organic layer from the quantum well, it was concluded that the energy transfer was mediated by dipole–dipole Förster coupling. Strong excitonic state mixing for an organic–inorganic quantum well heterostructure was demonstrated by measuring the energy branch splitting for polaritons in an optical microcavity . Outside of the cavity, strong coupling can only come about when the barrier between the organic layer and well is thin and the exciton wavefunctions overlap. , This criterion can be achieved by replacing the quantum well with a 2D semiconductor.…”
Section: Introductionmentioning
confidence: 99%